PERAN INOVASI DIGITAL DALAM MENINGKATKAN KINERJA PELAYANAN PUBLIK: STUDI PADA PENDAFTARAN NIKAH MELALUI SURABAYA SINGLE WINDOW (SSW ALFA) - Ais Zahrotun Kamila; Durinta Puspasari (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
Digital transformation in public services encourages local governments to improve service efficiency, effectiveness, transparency, and responsiveness through electronic-based systems. The Surabaya City Government developed Surabaya Single Window (SSW Alpha) as a digital public service innovation, including marriage registration services at the village administration level. This study aims to analyze the role of SSW Alpha digital innovation in improving public service performance in marriage registration services at Jagir Village, Surabaya City. The novelty of this study lies in its focus on the implementation of digital-based marriage registration services at the village level, which remains relatively underexplored in e-government studies. This research employed a descriptive qualitative method with data collection techniques consisting of observation, interviews, and questionnaires used as supporting data for triangulating users’ perceptions. The research informants included village officials and community members as users of the SSW Alpha service. The findings indicate that the implementation of SSW Alpha improves service time efficiency, accelerates administrative processes, facilitates real-time application monitoring, and enhances the organization of administrative data management. The digitalization of services has also transformed bureaucratic interaction patterns into more practical processes and reduced direct face-to-face interactions between the community and village officials. However, the implementation still faces several challenges, including system disruptions during login processes, application verification that has not been fully integrated, and limited digital literacy among elderly users and individuals unfamiliar with technology. The findings reinforce the concepts of e-government and Rogers’ diffusion of innovation theory regarding the importance of relative advantage, ease of use, and user readiness in supporting the success of digital public service innovation.